Local structural investigation of refractory oxide thin films near laser damage threshold. (15th April 2019) - Haque, S. Maidul; De, Rajnarayan; Tripathi, S.; Mukherjee, C.; Jha, S.N.; Bhattacharyya, D.
Highlights: RF sputter deposited thin films of TiO2, Ta2 O5, HfO2 and Gd2 O3 have been subjected to laser irradiation. Samples were irradiated by varying laser fluence or number of pulse shots across their damage threshold. XAFS and XANES measurements have been carried out on the irradiated spots of the samples. The effect on the local structure in the sample during the onset of laser damage has been studied thoroughly. Samples have also been characterized by optical microscopic imaging, GIXRD and GIXR measurements. Abstract: Study of laser induced damage mechanism and effort to increase the damage threshold of oxide thin films is of immense technological importance because as improved laser-damage resistant optical materials and better fabrication technologies are developed, laser designers can increase the system operating energies and powers to the limits of these new materials. Although, many efforts have been made to investigate how stoichiometry or long range order structure plays a role in describing the laser damage process, to the best of our knowledge, efforts to understand the local structural changes in the materials due to laser irradiation around the damage threshold has not been made so far. In this communication, a set of RF sputter deposited dielectric refractory oxide thin film samples have been subjected to laser irradiation across their damage threshold. In case of TiO2, Ta2 O5, and HfO2 thin films, the samples were irradiated with optimized laser fluence and different locations on the samples were irradiated with varying number of pulse shots, while in case of Gd2 O3 films, different locations of the samples were irradiated with fixed number of pulse shots and with varying laser fluence. The irradiated samples have subsequently been subjected to X-ray absorption spectroscopy (XAS) studies to find out change in the local structure of the samples under laser irradiation. Apart from XAS measurements, various other characterization techniques such as optical microscopic imaging, grazing incidence X-ray reflectivity and grazing incidence X-ray diffraction have also been employed to study the laser irradiated zones. The results indicate interesting local structural evolution in oxide thin films with the onset of laser induced damage which gives novel insight about the laser damage mechanism.